Radiation effects on rotating system free convective nanofluid unsteady flow with heat source and magnetic field - Manjunatha N; M.Girinath Reddy; Ahmad Aloqaily; Sarah Aljohani; A.Rupesh Reddy; Farhan Ali; Nabil Mlaiki (Partial Differential Equations in Applied Mathematics)
The analytical investigation delves into the intricate interplay between radiation, magnetic fields, and convective nanofluid flow within a rotating system that is subject to a heat source. The velocity along the plate is postulated to undergo oscillatory motion in the temporal domain, exhibiting a uniform frequency. In this particular experimental setup, the base fluids under consideration are water (H2O) and ethylene glycol (C2H6O2), while the nanoparticles being investigated consist of copper (Cu), titanium (TiO2), silver (Ag), and alumina (Al2O3). The analytical outcomes of the equations are derived through the utilization of perturbation methodology. The analysis and depiction of the impacts of the distinct factors are elucidated and visually represented in graphical form. The analytical discussions are undertaken to explore the impact of nanoparticles in the presence of radiation and rotating fluid on velocity, temperature profiles, skin friction coefficient, and Nusselt number. One observes the fluctuations in the velocity and thermal curves concerning various relevant physical parameters. The augmentation of the mass transpiration (suction) parameter intensity leads to an amplification in skin friction, thereby resulting in an enrichment of thermal transmission and a reduction in the temperature of the nanofluid. Moreover, it is demonstrated that the skin friction coefficient exhibits an augmentation as a consequence of mass suction and magnetic field, while concurrently witnessing decay in the thermal transmission rate.